Avaliação das condições da pele do recém-nascido em terapia intensiva neonatal - Schaefer, Tania Inez Mariga (2014)
In assisting the newborn (NB) preserving the integrity of the skin is an important aspect of care, as these predispose the newborn to the risk of acquiring infections. Maintaining the integrity of the skin of the newborn in the Neonatal Intensive Care Unit (NICU) becomes a challenge because of the various procedures that they are exposed. Monitoring the condition of the skin serves to guide care and should be performed carefully by professional and objective and systematic way. This study was to evaluate the general conditions of the skin of hospitalized newborns in the NICU. This is a longitudinal study with quantitative descriptive approach, conducted in a NICU, located in the southern Brazil. The data collection was carried out through a characterization form of clinical newborn and application of Neonatal Skin Condition Score NSCS. Which ranks the newborn skin conditions, with the score 3 to better skin condition and the score 9 to worse skin condition of the newborn. Data were organized in Excel software, with double entered independently. After correction of errors and inconsistencies analysis was performed using SPSS version 20.0 Statistics Program. The development of the study met national and international standards of ethics in research involving human beings. The study included 47 newborns. Prevailed premature newborns, male, born by cesarean delivery weighing up to 1500 g. As for the evaluation of skin conditions, from the constructs of NSCS, around 23% had dry skin; about 32% had erythema and 74.5%, breakage/damage in small localized areas. In total scores showed 42.6% and 40.4% score 4, 5 score. Associating variables with the scores showed newborns statistical significance for the development of skin lesions, extreme prematurity, low birth weight and newborns using PICC and peripheral concurrently. It was concluded that the predominant score 3 indicates a positive assessment of the skin of these infants. However, among the highest scores rupture injury was prevalent construct and is related to peripheral venous punctures.